Evaluating inhibitory potential targeting cholesteryl ester transfer protein (CETP) by hydroxycitric acid (HCA) found in garcinia species through kinetic and in-silico technique - Abdul Sani, Suraya (2016)
Cardiovascular disease has emerged in developing countries and becoming the leading cause of death recorded. Many scientific studies have been conducted in order to understand the specific mechanism on how atherosclerosis develop, searching for the real culprit that responsible in the progression of the disease and suggesting the possible prevention to overcome this problem. This piece of work examined and revealed the mechanism of action on how secondary metabolites that has been isolated from Malaysian local plants which have the properties to impede the action of cholesteryl ester transfer protein (CETP) in order to prevent the atherosclerosis. Preliminary results of the crude plant extracts from the initial screening showed positive results. A similar trend of inhibition can be obtained for twigs and leaves extracts of Garcinia atroviridis and Garcinia parvifolia. Ethanol extracts of fruit parts of Garcinia atroviridis give IC50 of 19.28 ± 0.021 mg/ml which shows the highest inhibitory compared to the other extracts of other plant parts. The remarkable results that are obtain from fruit rinds of Garcinia atroviridis do give some hints that the secondary metabolites that are present might have the ability to inhibit CETP. Based on literature review, it is postulated hydroxycitric acid (HCA) might be responsible for inhibiting CETP activity and HCA has been selected for further studies. Kinetic studies have been employed in this piece of work in order to see the types of inhibition that HCA possess against CETP. The kinetic study has revealed that HCA is a noncompetitive inhibitor because of the Km (-0.12) that is unchanged for every substrate and the Vmax is increased when the concentration of the inhibitor increase. Further in-silico works such as molecular docking and molecular dynamic has been implemented as well in order to see the interaction and mechanism of action between HCA and CETP. The molecular docking work has revealed that HCA binds to the same side as torcetrapib does and the RMSD obtained was 2.703Å. Molecular dynamics has been employed as well in order to see the extensive structural and functional analysis and also to evaluate the strengthness of the complex between HCA and CETP. The complex were found to be stable due to the existence of the hydrogen bonding to SER230 and the overall RMSD reading are between the range of 0.8Å, 2.4Å and 3.2Å. Overall, this work are pioneering and pave the way for further studies in establishing a new chemical template form of natural products for CETP research with an objective to extend the scope of work into in-vivo studies and x-ray crystallography in order to enable us to understand the mechanism of action in protein level. The in-silico studies in this work provides a preliminary understanding on the structural basis of CETP structure and its active sites which could accommodate the exact template of chemical molecule. With this new understanding, an inhibitor drug which are effective with lesser side effect, targeting atherosclerosis could be developed.